2020
DOI: 10.1097/pec.0000000000002241
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes With Febrile Neutropenia Based on Time to Antibiotics in the Emergency Department

Abstract: Objective: Although bacteremia in pediatric oncology patients with febrile neutropenia (FN) is not uncommon, sepsis and mortality are rare. Because of the lack of clinically meaningful decision tools to identify high-risk patients with bacteremia, time to antibiotic administration (TTA) is increasingly considered an important quality and safety measure in the emergency department. Because little evidence exists suggesting that this benchmark is beneficial, we sought to determine whether TTA of 60 minutes or le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…These results are in accordance with several recent studies assessing the impact of TTA in smaller cohorts of pediatric patients with FN. 23,26,32 A few FN studies have shown an association between a prolonged TTA and some adverse clinical outcomes but have not been consistent. 39 Fletcher et al showed in 1,628 FN episodes a multivariate association between a composite outcome (death, ICU admission or receiving >40 mL/kg IVF) in those receiving antibiotics between 60 and 120 minutes (32.9% of the cohort) versus ≤60 minute (20% of the cohort), P 5 .048.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in accordance with several recent studies assessing the impact of TTA in smaller cohorts of pediatric patients with FN. 23,26,32 A few FN studies have shown an association between a prolonged TTA and some adverse clinical outcomes but have not been consistent. 39 Fletcher et al showed in 1,628 FN episodes a multivariate association between a composite outcome (death, ICU admission or receiving >40 mL/kg IVF) in those receiving antibiotics between 60 and 120 minutes (32.9% of the cohort) versus ≤60 minute (20% of the cohort), P 5 .048.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with several recent studies assessing the impact of TTA in smaller cohorts of pediatric patients with FN. 23,26,32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Other studies examining outcome have not demonstrated similar benefits in terms of mortality or reduced need for ICU level of care. 10,11 Nevertheless, the window of "antibiotics within 60 minutes" continues to be viewed as a quality of care metric for immunocompromised oncology patients with fever. [12][13][14] There are a number of published studies highlighting efforts to reduce the time to antibiotics for febrile pediatric oncology patients.…”
mentioning
confidence: 99%
“…Some have demonstrated that lower TTA is associated with reduced rates of mortality, reduced need or time in intensive care unit (ICU) settings, reduced hospitalization length of stay, and, as a result, lower overall cost of care 8,9 . Other studies examining outcome have not demonstrated similar benefits in terms of mortality or reduced need for ICU level of care 10,11 . Nevertheless, the window of “antibiotics within 60 minutes” continues to be viewed as a quality of care metric for immunocompromised oncology patients with fever 12–14 …”
mentioning
confidence: 99%